Financial Ratio and Market Reaction Before and During The Covid-19 Pandemi : Evidence from Hotel, Restaurant, and Tourism Companies in Indonesia - Maulidia, Sabrina Ayuni; Yulianto, Agung; Sulistyowati, Wiwit Apit (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to analyze differences in company financial performance which includes profitability ratios, liquidity ratios, and stock prices in 2018-2019 (before the Covid-19 pandemic) and 2020-2021 (during the Covid-19 pandemic). The population in this research are companies that are listed in the hotel, restaurant, and tourism sub sector on the Indonesia Stock Exchange (IDX). The sample was selected using a purposive sampling method and the final sample was 22 companies with 88 units of analysis for 4 years. The statistical analysis method used in this research is the Wilcoxon Signed Ranks Test. In this research, profitability ratios were measured using Return on Equity (ROE), liquidity ratios were measured using Current Ratio (CR), and stock prices were measured using closing price. The results of this research prove that there were significant differences in the profitability ratios before and during the Covid-19 pandemic, there were significant differences in the liquidity ratios before and during the Covid-19 pandemic, and there were significant differences in stock prices before and during the Covid-19 pandemic. The results of this research indicated that the most of the companies sampled had decreased profitability, liquidity, and stock price before and during pandemic Covid-19.